O regime jurídico das Parcerias para o Desenvolvimento Produtivo de medicamentos - Glassman, Guillermo (2020)
This research describes the legal framework of the public-private drug partnerships (PDP). It is an agreement model developed by the Ministry of Health to encourage the incorporation of strategic technologies by the Brazilian official pharmaceutical laboratories (LFO), put into operation since 2009. The main tool of this policy is the establishment of public market reserves for products manufactured jointly by the public and private partners. With this agreement, the Federal Government intends to oppose the vulnerability of SUS in the technological area and, thus, to strengthen the productive chains of the Industrial Health Economic Complex – creating important positive externalities. However, the legal complexity of the model, the absence of a legal basis specifically designed to support it, and the parsimonious attention it has received from the academy call into question its regularity, giving rise to a heavy burden of legal uncertainty. Such circumstances considered, we sought to contextualize the normative foundations of the PDP, verifying their legal validity. On the other hand, this research analyzes the limits in which the model maintains its compatibility with the legal framework. This is because it is possible to identify regularity parameters for the definition of: the strategic technologies that can be the object of partnerships; the minimum scope of technological training services; the most appropriate way for the selection of the private partner; the criteria for approval of partnerships by the Ministry of Health; the distribution of public demand among the approved partnerships; the elements that compose the economic balance of these partnerships; the sales prices of products manufactured during the technology transfer process; and other relevant aspects of the PDP. This mapping is important, especially because, applied in the wrong way, this partnership model loses its original function and can become an bid fraud, in an administrative counterfeiting. Given this scenario, this research indicates solutions to the problems identified in the legal framework of PDP, presenting the correct guidelines that must be adopted for their proper functioning. In these terms, the PDP can make a relevant contribution to the pharmaceutical policy of SUS. This research, therefore, allows a management of the PDP with a higher degree of legal certainty, seeking, for this, to diagram the legal framework of the PDP and its specificities, contributing to overcome the situation of uncertainties that appears at first sight